2015
DOI: 10.3389/fmats.2015.00011
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Nano-Ductility of Glasses: The Critical Role of Composition

Abstract: Understanding, predicting, and eventually improving the resistance to fracture for silicate materials is of primary importance to design tougher new glasses suitable for advanced applications. However, the fracture mechanism at the atomic level in amorphous silicate materials is still a topic of debate. In particular, there are some controversies about the existence of ductility at the nanoscale during crack propagation. Here, we present simulations of fracture of three archetypical silicate glasses, using mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 46 publications
12
74
0
Order By: Relevance
“…Due to the limited availability of realistic inter-atomic potentials (that can encompass any combination of elements), the compositions of the simulated systems were restricted to the following oxides: SiO 2 and Al 2 O 3 (network forming species), and CaO, MgO, Na 2 O, K 2 O (network modifying species), while maintaining the molar ratios among these oxides as equivalent to the native fly ashes. [28][29][30] The T A B L E 2 Relative abundance of crystalline compounds of the fly ashes measured by quantitative X-ray diffraction and Rietveld refinement (mass%), and the corresponding standard errors 16 It is well-known that the glassy phase of fly ash is not homogeneous. 26 The simulations were performed with a timestep of 1 fs using the interatomic potential parametrized by Teter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the limited availability of realistic inter-atomic potentials (that can encompass any combination of elements), the compositions of the simulated systems were restricted to the following oxides: SiO 2 and Al 2 O 3 (network forming species), and CaO, MgO, Na 2 O, K 2 O (network modifying species), while maintaining the molar ratios among these oxides as equivalent to the native fly ashes. [28][29][30] The T A B L E 2 Relative abundance of crystalline compounds of the fly ashes measured by quantitative X-ray diffraction and Rietveld refinement (mass%), and the corresponding standard errors 16 It is well-known that the glassy phase of fly ash is not homogeneous. 26 The simulations were performed with a timestep of 1 fs using the interatomic potential parametrized by Teter.…”
Section: Methodsmentioning
confidence: 99%
“…27 This potential has been extensively studied and has been shown to predict realistic glass structures. [28][29][30] The T A B L E 2 Relative abundance of crystalline compounds of the fly ashes measured by quantitative X-ray diffraction and Rietveld refinement (mass%), and the corresponding standard errors 16 Calcio-olivine 0.43 It is well-known that the glassy phase of fly ash is not homogeneous. This assumption excludes any effects which may arise from a heterogeneous mixture of glassy and crystalline phases as is present in fly ash.…”
Section: Methodsmentioning
confidence: 99%
“…The energy release rate ( G C ) and fracture toughness ( K IC ) are the most important properties, which can be estimated using MD simulations, because these properties define criteria of crack initiation and propagation on fracture mechanics simulations, such as eXtend finite element method and Peridynamics, which are sophisticated techniques to describe discontinuous crack propagation and fracture using continuum methods. Indeed, recently it has confirmed that K IC of oxide glasses are predictable by simulating crack propagation using MD simulations …”
Section: Introductionmentioning
confidence: 91%
“…Indeed, recently it has confirmed that K IC of oxide glasses are predictable by simulating crack propagation using MD simulations. [33][34][35][36][37] Furthermore, very recently, Zhang and Shahsavari have demonstrated a number of fracture simulations on calciumsilicate-hydrate (concrete), in which portlandite nanoparticles and also nanovoids are randomly dispersed, using MD simulations, in order to understand the role of the nanostructures on fracture mechanism. 38 On the other hand, to the best of our knowledge, there is no study investigating nanoparticles reinforced amorphous oxide glasses using atomistic simulations so far.…”
Section: Introductionmentioning
confidence: 99%
“…For amorphous solids a correction factor must be applied to account for the inherent ductility of the structurally disordered material. Comparison of the results of Wang et al 35) with Tromans and Meech indicate a consistent increase in fracture energy for silica, sodium silicate, and calcium aluminosilicate glasses over G IG , G GB , and G IP of ~1.63, ~1.78, and ~1.96, respectively; this covers the entire structural landscape of silicate glasses. These theoretical results are consistent with the result of Purwanto et al which found fracture of RCA slag (amorphous) required ~1.82 times more energy than water-impinged slag (ostensibly a mixture of IG, GB, and IP fractures).…”
Section: )mentioning
confidence: 59%